PROBLEMS OF LEGAL REGULATION OF THE PROCEDURE FOR ORGANIZING THE TRANSPORTATION OF PASSENGERS AND BAGGAGE BY ROAD - Maliarchuk, Nazar (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to carry out a legal analysis of the provisions of Order of the Ministry of Infrastructure of Ukraine dated 15.07.2013 No. 480 “On Approval of the Procedure for Organization of Passenger and Luggage Transportation by Road”. The research methods are to analyze the procedure for regulatory regulation of passenger traffic surveys to study the demand or determine the level of satisfaction of the population’s needs by passenger road transport, to study the problems of the regulatory and legal procedure for implementing the opening of new bus routes in Ukraine, to assess the effectiveness of the procedure for organizing passenger transportation by road transport at the present time. Results: the analysis of the legal and regulatory framework governing the organization of passenger and luggage transportation by road has revealed individual and systemic shortcomings in ensuring the rights of both carriers and passengers in the context of exercising the right to conduct business activities with the opening of new routes, and passengers in relation to road safety and the choice of passenger boarding and disembarkation points. According to the results of the study, there is a need to update the regulatory framework in the field of passenger transportation by road. Discussion: the analysis of the subject matter of the study indicates the need to bring the regulatory framework in line with the requirements and challenges of today’s passenger transportation by road. Taking into account the gaps and shortcomings, it is important to develop and implement effective control mechanisms that will ensure compliance with norms and standards in the course of economic activity by business entities (road carriers), which in turn will help to improve the conditions of passenger transportation, ensure and increase the demand for transport services.